Aqueous electrospinning of poly(2-ethyl-2-oxazoline): Mapping the parameter space. (March 2017) - Stubbe, Birgit; Li, Yin; Vergaelen, Maarten; Van Vlierberghe, Sandra; Dubruel, Peter; De Clerck, Karen; Hoogenboom, Richard
Graphical abstract: Highlights: Aqueous electrospinning of poly(2-ethyl-2-oxazoline). Successful fiber formation with low molar mass polymers. Fiber thickness tunable by concentration and polymer molar mass. Upscaling of electrospinning up to several square meters. Abstract: Recently, poly(2-oxazoline)s have regained significant interest and research has especially been focusing on biomedical applications. As non-woven nanofibrous mats show appealing features in this respect, the potential and limitations of electrospinning aqueous solutions of poly(2-ethyl-2-oxazoline) (PEtOx), the only poly(2-oxazoline) produced on industrial scale ( i.e. Aquazol®) so far, was evaluated. The polymer molecular weight appeared to be the dominant factor defining the optimal concentration range for successful nanofiber production. The molar mass distribution, i.e. the dispersity (Ð), is relevant as well. However, it is not a limiting factor as defined PEtOx (Ð < 1.2) could be electrospun without major adaptations to the electrospinning procedure that was optimized for the commercial grades of Aquazol® with Ð of 3–4. By varying the PEtOx molecular weight and concentration, a broad range of fiber diameters can be targeted. Furthermore, we demonstrated the transferability of the PEtOx electrospinning parameters and the reproducibility of the resulting fiber diameters by repeating the experiments on an independent mononozzle electrospinning device, by a different operator. In order to fulfil all prerequisites for industrialization, we also demonstrated the feasibility for upscaling the PEtOx nanofiber production process using a pilot scale multinozzle electrospinning set-up.